Temporary Nasal Morbidity after Expanded Endoscopic Endonasal Surgery for Skull Base Tumors - Chiramal, Lidia Dennis; Sundarasan, Rajan; Chacko, Ari G.; Thomas, Regi (Journal of Neurological Surgery Part B: Skull Base, 2024)
To assess olfactory dysfunction and quality of life (QOL) in patients undergoing expanded endoscopic endonasal approach for skull base tumors.Prospective observational study of patients undergoing expanded endoscopic endonasal approach for anterior skull base and pituitary lesions from 2018 to 2019.Christian Medical College and Hospital, Vellore, Tamil Nadu, India.A total of 29 consecutive patients who underwent expanded endoscopic endonasal approach.Olfactory function and QOL were assessed using Connecticut Chemosensory Clinical Research Centre olfaction test and Sino Nasal Outcome Test 22 questionnaire, respectively, preoperatively and at the 2nd week and 3rd month postoperative follow-up.Olfaction scores significantly worsened in the 2 weeks postoperative period compared with the preoperative scores. By 3rd postoperative month 48% of the patients returned to baseline, 48% had only mild hyposmia, and only 1 patient had persistent moderate hyposmia. QOL scores significantly worsened in the immediate postoperative period and although they improved over 3 months, they did not reach baseline.Expanded endoscopic endonasal approaches to the anterior skull base cause transient olfactory dysfunction and nasal morbidity in the immediate postoperative period. Although olfactory function and QOL scores improved in the majority of patients, at least 50% had mild residual dysfunction at 3 months postoperatively. Olfactory epithelium-preserving surgical techniques, adequate endoscopic nasal cleaning postoperatively, and good nasal douching are factors that help improve olfactory function postoperatively.
Keywords: olfaction; nasal morbidity; expanded endoscopic surgery; SNOT-22; skull base surgery